A Literature Review of Depression and Anxiety in Breast Cancer Patient - Indah, Crisnah (HM Publisher, 2023)
Breast cancer that is one of the most common cancers experienced by women (adult or elderly) has a great effect on the patient's psychology. The most common psychological problems found in breast cancer patients are depression and anxiety. Many factors affect the incidence of depression and anxiety, such as lack of family support, lack of social support, prolonged therapy, changes in body shape, divorce, income and age. There are several ways to diagnose depression and anxiety in cancer patients, such as a distress thermometer or Patient Health Questionnaire (PHQ)-4. Actually, depression and anxiety disorders have a poor impact on these patients. There are several alternative non-pharmacological therapies that can be chosen, like cognitive behavioral therapy, family support and social support.